Efeito dos hormônios tireoidianos no perfil angiogênico e imune da decídua e glândula metrial de ratas e seu impacto na decidualiação, vascularização e população de células uNKs na interface materno-fetal - Cintia Almeida de Souza (2017)
During gestation, the decidua and metrial gland coordinate the placentation process, allowing the selective exchange of nutrients and metabolites between mother and fetus, and provides subsidy for the semi-allogeneic embryo/fetus to remain in close contact with the uterus. But for the success of gestation, it is essential that there is a coordinated interaction between the placenta and the uterus by various hormones, among which thyroid hormones. Two different experiments were performed. The first one was goal to evaluate the decidualization and expression of angiogenic factors and the second one evaluates the spatiotemporal expression profile of immunological factors and the uterine Natural Killer cells (uNKs) in the decidua and metrial gland of rats with hypothyroidism and treated with L-tyroxine (T4). For the first experiment, 72 adults Wistar rats were distributed in the hypothyroid, T4 treated and control groups. At 10, 14 and 19 days of gestation (DG), the decidua and metrial gland were collected for histomorphometric and immunohistochemical evaluation of vascular endothelial growth factor (VEGF), Flk-1 and Tie-2 expression. For the second experiment, 108 adults Wistar rats were distributed in three experimental groups, hypothyroid, treated with T4 and control. The rats were euthanized at 7, 10, 12, 14 and 19 DGs. The immunohistochemical detection of IFN, MIF, IL15, iNOS and the labeling with Lectin DBA were evaluated for the detection of uNK DBA+ cells in the decidua and metrial gland. In addition, the expression of Ifn, Il15 and iNos by real-time RT-PCR was evaluated. Data from both experiments were analyzed by the Student-Newman-Keuls (SNK) test. In the first experiment, it was shown that hypothyroidism reduced the decidua area at 10 and 19 DG. In addition, VEGF increased at 10 and 14 DG and Flk-1 only at 14 DGs in the hypothyroid animals, but both were reduced to 19 DGs in the metrial gland, without significantly altering the area occupied by the blood vessels. The rats treated with T4 showed an increase in the number of deciduous blood vessels at 10 and 19 DG. In addition, at 10 DGs, excess T4 resulted in the increase of Flk-1 in the decidua and in the metrial gland. Hypothyroidism increased Tie-2 at 10 and 19 DGs in the decidua and metrial gland. The second experiment showed that the expression of pro and anti-inflammatory factors studied oscillated throughout gestation in all groups, both in the decidua and in the metrial gland. Hypothyroidism increased the protein expression of iNOS at 7 DGs, IL15 and MIF at 10 and 12 days, IFN and MIF at 14 DGs in the decidua and/or metrial gland and the gene transcripts for iNos at 12 and 19 DGs and for Ifn and Il5 To 14 DGs. In addition, hypothyroidism reduced the protein expression of the proinflammatory factors MIF, at 7 DG, and IFN at 12 days, and of the gene transcript for Ifn at 10 and 19 DGs. Hypothyroidism also reduced the protein expression of the anti-inflammatory factor iNOS at 12, 14 and 19 DG and reduced its gene transcripts at 10 and 14 DGs. The T4 treated groups showed increased expression of IFN, IL15 and MIF at 7 DG, IL15, iNOS and MIF at 10 DG, MIF at 12 DGs in the metrial gland, IFN and MIF at the baseline decidua at 14 DGs. In addition, treatment with T4 reduced the protein expression of IFN at 12 and 19 DG, IL15 at 12 and 14 DG and iNOS at 12 and 14 DGs. At 7 and 10 DG there was a reduction of migration of uNK DBA+ cells to decidua in both treatment groups. However, at 12 DG there was an increase in the group treated with T4 and at 14 DG a reduction in the hypothyroid group. It can be concluded from the first experiment that hypothyroidism reduces the decidua area and increases the expression of VEGF, Tie-2 and Flk-1. Excess T4 promotes tissue angiogenesis by increasing the number of vessels in the decidua associated with increased expression of Flk-1. With the second experiment it was concluded that both hypothyroidism and thyroxine treatment altered the spatiotemporal expression profile of the immunological factors of the decidua and metrial gland throughout pregnancy. The reduction of the proinflammatory factors IFN and IL15 is more predominant in the group treated with T4, whereas hypothyroidism compromises the development of an anti-inflammatory environment at 24 the feto-maternal interface, since the reduction of the anti-inflammatory factor iNOS and of the uNK DBA+ cells is mainly evidenced in this group.